PERLINDUNGAN HAK CIPTA DALAM TRANSAKSI DAGANG INTERNASIONAL - Niken Prasetyawati (Institut Teknologi Sepuluh Nopember, 2011)
Globalization in commerce is an impact of advance of technology which causes global community to close and rely on another. Getting in touch in the field of economic activity requires the existence of business law harmonization across border including agreed arrangement of playing level. Applied arrangement in international commerce is GATT/WTO system.Since Indonesia ratified WTO international trade convention, this reality has placed Indonesia into point of no return potition. It meant that Indonesia mandatory to follow and comply with all arrangements prevail to all WTO’s member states with its consequences, including the commitment of Intellectual Proprty Rights.